Clinical, biochemical, and histological studies of osteomalacia, osteoporosis, and parathyroid function in chronic liver disease. Issue 2 (February 1978) - Long, R G; Meinhard, E; Skinner, R K; Varghese, Z; Wills, M R; Sherlock, S
Abstract : Twenty of 32 patients with either chronic cholestatic or hepatocellular liver disease had bone pain or recent fractures. On bone biopsy five patients had normal bone, 15 had osteomalacia, five had osteoporosis, and seven had a combination of osteomalacia and osteoporosis. In the presence of osteoporosis, osteomalacia was minimal or absent. There was no biochemical, radiological, or histological evidence of excess parathyroid activity. No significant correlations were demonstrated between the plasma and urinary biochemical findings and the presence of either osteoporosis or osteomalacia and bone biopsy was essential for correct diagnosis. There was no statistical relationship between low serum 25-hydroxy vitamin D values and the presence of osteomalacia. Bone disease was not prevented by regular intramuscular vitamin D2, although biochemical changes were improved. Drugs such as corticosteroids and cholestyramine may be important aetiological factors in hepatic osteodystrophy.